Peran Guru PAI Sebagai Agen dalam Pencegahan Informasi Hoax pada Siswa Tingkat SMK - Wulandari Rahmadana; Anisa Misrida; Zubaidah (At-Tadris: Journal of Islamic Education, 2025)
This study aims to determine the role of Islamic Religious Education teachers in preventing hoax news for vocational high school students. This research method uses descriptive qualitative research with data collection through observation and interviews. The results of this study reveal that the role of Islamic Religious Education teachers in disseminating hoax information to students has not been implemented, only carried out by teachers personally when entering class hours. However, in general, schools provide appeals to students including; Students are not allowed to bring communication devices such as cellphones and the information is distributed in each student's class group, displaying hoax posters and. Attaching hoax-themed wall magazines (madding) with the aim that students at SMKN 1 Singkil Utara can avoid hoax information.